MELTING AND DISSOLUTION OF SUBDUCTING CRUST AT HIGH PRESSURES: THE KEY ROLE OF WHITE MICA - Schmidt M.W.; Vielzeuf D.; Auzanneau E. (My University, 2004)
Conditions of melting in the crust are generally controlled by the availability of aqueous fluid and, in the absence of fluid, by the stability of hydroxylated minerals. To depths of 80–90 km, melting is controlled by amphibole and biotite. At greater depths, both phases are unstable in crustal compositions. Simultaneous experiments on a mid-ocean ridge basalt (MORB), a greywacke, and a pelite with excess H2O of 0.4–1.4 wt.% demonstrate that, at N100 km depth (z3.5 GPa), all three bulk compositions are composed of garnet+clinopyroxene+phengite+coesiteFkyaniteFrutile, phengitic white mica being the only hydrous mineral present at near-melting temperatures. At 4 GPa, melting reactions, temperatures, and initial melt compositions are thus similar in the entire subducted crust. Fluid-saturated initial melting takes place near 850 8C and melt productivities are proportional to phengite contents. All three bulk compositions produce initially slightly peraluminous potassic Si-rich granites with K:Na molar ratios of 1.4–2.0 and containing 8–13 wt.% H2O. The relatively low Na-contents of these melts result from clinopyroxene/melt partitioning coefficients (Dcpx/melt) of 2.2–4.0 at near solidus temperatures. At higher pressures (z6.5 GPa), we infer that classical melting does not take place. Instead, the bulk H2O-contents (1.5–2.1wt.%) in the starting materials, although low, are apparently sufficient to dissolve phengite entirely near 1050 8C. This suggests that pressure conditions beyond the singular endpoint (or second critical point) which terminates the wet solidus as defined by Ricci in 1951 [J.E. Ricci, The phase rule and heterogeneous equilibrium, Dover Publications, Inc. New York (1951) 505 p.] were reached for all three bulk compositions. Extraction of these bsupercriticalQ solute-rich (but Na-poor) melts, which contain about 30–40% H2O, or extraction of the potassic granite melts at lower pressure leave an anhydrous garnet+clinopyroxene+coesite+kyanite+rutile residue. Our results suggest that, except for extremely cold subduction zones, the subducting crust will lose all its potassium (and most of B, Be, Rb, and Ba, and other phengite-hosted trace elements) through leaching or melting during its descent to 300 km. The potassium-rich silica-saturated liquids will immediately react with the peridotite when entering the mantle wedge thus creating source regions for ultrapotassic magmas.